Alexithymia In A Relapsing Addict - شناوي, رزيقة; ملال, خديجة (مجلة دراسات في سيكولوجية الانحراف, 2021)
Drug addiction is one of the most important problems that affect many people and societies, and upset their balance. This study dealt with the topic of alexithymia in a relapsing addict in order to highlight the emotional role played in the regression of the addict. For this reason, a clinical study on a relapse addict has been carried out who was following treatment at Chlef Mediator center for addiction treatment, with the use of the following tools: the half directed interview, observation, TAS20 Alexithymia standard. It was found that the relapsing addict has a high alexithymia level in all dimensions: after describing emotions’ difficulty,